SUPER WOMEN: SOLUSI TERHADAP KEKERASAN PADA PEREMPUAN? - M.Hum, Syamsudin, (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2009)
Violence on women will never stop! This statement could be right looking at the recent condition experienced by women. There are at least two factors causing women always become the victim of many violence and are always marginalized. The first factor because of the patriarchy culture system and the second one, because of the inappropriate interpretation of Koran verses.Â Those two factors really have placed women to be weak in many aspects of life. Moreover, they only have low education. They become passive and dependent. They are even as weak as their physic compared with men. Thatâ€™s why, they are easy to become the victim of many violence. Danger is always staying in front of them. But, knowing about this, canâ€™t women free themselves from this bad condition? The answer is clear; Yes, they can! But what to do? There is only one thing that can help women free from being colonialized. Whatâ€™s that? â€œSuper Womenâ€ ! Right, â€œSuper Womenâ€ is the only answer for them to be free from being the victim of many violence and being marginalized in many aspects of life. But, to become â€œSuper Womenâ€ is not easy.Â To be â€œSuper Womenâ€, they must get high education. However, there is nothing impossible in this world. Thatâ€™s why, they must educate themselves soon.Â Using the knowledge they get they can change their world. Next, their life wonâ€™t be filled with story of becoming the victim of many violence or being marginalized, on the reverse, theyÂ could manage their own life to be â€œSuper Womenâ€. And only by becoming â€œSuper Womenâ€, based on the religion corridor women would be successful in career, social organization and household fully. Finally, they could maximize their life to be useful for themselves, family, society and the country.Key Terms: violence on women, education, â€œSuper Womenâ€.Â Â